Postnatal Midwifery Care for Mrs. "I" with Complaints of Breast Milk Congestion at Bungi Health Center - Aisyah; Sitti Aisyah Ansi; Asriadi (International Journal of Multidisciplinary Learners, 2025)
Background: Breast engorgement is an event where the venous and lymphatic flow is blocked, the flow of milk becomes obstructed and pressure on the breast milk ducts (alveoli) increases. This event is caused by the accumulated milk not being released so it becomes blocked. In Indonesia, the incidence of mothers experiencing breast engorgement is still very high. Objctive: This study aims to implement postnatal midwifery care for Mrs. "I" who experienced breast milk engorgement at Bungi Health Center, Baubau City. Sample/Research Object: The subject of the study was Mrs. "I", a patient who experienced breast milk engorgement. Method: This study used a case study method with the Varney 7-step and SOAP approaches. Data collection was carried out through primary and secondary data. The stages of the study include assessment, identification of actual diagnoses/problems, identification of potential problems, immediate action, care planning, implementation of care, evaluation, and documentation. Results: The results of the case study showed that there were no obstacles in handling breast milk engorgement in Mrs. "I". The entire management process went smoothly without complications, both for the mother and the baby. Vital signs were within normal limits, indicating good health conditions. Conclusions : This study emphasizes the importance of implementing Varney’s 7-step management and documentation in SOAP format to ensure effective and professional midwifery care. It is expected that midwives can provide quality services without distinguishing the patient’s social status.